Opinion polls and public opinions in Japan's foreign policy, do they matter? - Chau, Noel Song Yeen (2019)
This dissertation investigates the linkages between public opinion and policy, within two specific contexts, within the spheres of foreign policy and Japanese politics. This dissertation, through a critique of existing literature review regarding public opinion and its impact on foreign policy, within the context of Japan, argues that existing theories and literature are inadequate in explaining how public opinion can impact Japan’s foreign policy. The primary focus of this dissertation is to critically examine oft-cited axioms regarding public opinion and policymaking, where I assert that there is a lack of breadth in the field of work conducted on this topic, especially in the context of Japan. A goal of this dissertation is to illustrate how this lack translates to incomplete conclusions on the impact of public policy where scholars often either overdetermine the impact of public opinion or relegate public opinion as inconsequential. This dissertation intends to suggest directions in how such a lack can be remedied.